Seroprevalence of Toxoplasmosis in Pregnant Women Admitted to the Health Centers of Khorram-Abad City, Iran - Kurosh Cheraghipour; Heshmatollah Taherkhani; Mohammad Fallah; Ali Sheikhian; Khosro Sardarian; Mohammad Rostami Nejad; Amirhosein Maghsood (پزشکی بالینی ابن سینا, 2010)
Introduction & Objective: Toxoplasmosis is one of the most widespread parasitic infections in humans that can cause abortion in pregnant women or serious damage to their fetuses. To determine the seroprevalence of toxoplasmosis in pregnant women of Khorram-Abad,a city in the west of Iran, a cross sectional study was performed by random cluster sampling of pregnant women admitted to rural and urban health centers of Khorram-Abad during 2006 to 2007. Materials & Methods: After recording 390 volunteers’ information in the questionnaires and preparation of the samples, prevalence of current/recent toxoplasmosis was evaluated by an enzyme-linked immunosorbent assay (ELISA) technique for the detection of toxoplasma-specific IgM, and previous history of infection by IgG. Results: This study revealed that the IgG seroprevalence of toxoplasmosis in urban and rural pregnant women of Khorram-Abad was 30.8% and 31.4%, respectively and that of IgM seroprevalence was 7.2% and 7.9%, respectively. However, IgG antibody levels increased with age (P<0.001). Education level of women was associated with the level of both antibodies (P<0.01). No statistically significant differences were observed in the levels of antibodies in relation to other study variables. Conclusion: According to this study, 69% of the pregnant women were seronegative and consequently are susceptible to acute toxoplasmosis and subsequent injury to their fetuses. So because of the importance of toxoplasmosis in pregnant women, public health education is necessary for prevention of this serious opportunistic infection.